Second-type disorder in colloidal crystals - Dullens, R; Petukhov, A (2007)
The presence of second-type disorder in self-organised colloidal crystals is demonstrated on the basis of confocal microscopy. The study is performed for crystals consisting of colloidal hard spheres and hard polyhedral colloids. Using confocal microscopy single-crystalline domains were imaged and the particle coordinates were retrieved using particle tracking routines. To distinguish different types of disorder present in the crystals the corresponding diffraction patterns were computed from the real-space coordinates. We show that second-type disorder is present in the crystals of both the spheres and the polyhedrals. The amount of second-type disorder is significantly larger in the crystal of the polyhedrals. This shows that colloidal crystals form an ideal model system to study various types of disorder since the analysis is possible in both real and reciprocal space. Simulating diffraction patterns from real-space coordinates therefore provides a useful route to a better understanding and interpretation of diffraction patterns. Copyright © EPLA, 2007.